Safety and immunogenicity of a fully-liquid DTaP-IPV-Hib-HepB vaccine (Vaxelis™) in premature infants - Marissa B. Wilck; Z. Jin Xu; Jon E. Stek; Andrew W. Lee (Taylor & Francis Group, 2021)
Background: Immune immaturity may put premature infants at increased risk for infections. DTaP-IPV-Hib-HepB vaccine (Vaxelis™), a hexavalent vaccine studied in >6,800 children, has acceptable safety and immunogenicity profiles generally similar to control vaccines. Here we evaluate safety and immunogenicity of DTaP-IPV-Hib-HepB vaccine in premature infants. Methods: Premature infants were identified using prior medical conditions terms "premature baby/delivery" and/or "low birth weight baby". Immunogenicity and safety data were summarized across one Phase II and four Phase III randomized, active-comparator-controlled clinical trials (Protocol 004 in Canada [Control: PENTACEL™]; Protocols 005 and 006 in the US [Control: PENTACEL™]; and Protocols 007 and 008 in the EU [Control: INFANRIX™ hexa]) and one Phase III clinical trial in the UK (PRI01C); no formal statistical comparisons were performed. Results: Overall, 160 infants were considered premature (DTaP-IPV-Hib-HepB = 111 Control = 49). The incidence of adverse events (AEs) for DTaP-IPV-Hib-HepB was comparable between overall and premature populations for all AEs days 1-15 postvaccination (Overall = 96.3%; Premature = 97.3%;), solicited injection-site AEs days 1-5 postvaccination (Overall = 84.1%; Premature = 75.5%), and solicited systemic AEs days 1-5 postvaccination (Overall = 93.7%; Premature = 94.5%). A high percentage of premature infants mounted protective immune responses to antigens contained in DTaP-IPV-Hib-HepB vaccine. Response rates in preterm infants for all antigens (80-99%) were in a similar range to all infants (80-99%) for both DTaP-IPV-Hib-HepB and control vaccines. Conclusions: DTaP-IPV-Hib-HepB vaccine has a low incidence of AEs, an acceptable safety profile, and elicited satisfactory immune responses in premature infants comparable to the overall study population. These findings support vaccination with DTaP-IPV-Hib-HepB vaccine in healthy premature infants.